Lean management practices in Malaysian local government / Nur Ain Abu Bakar - Abu Bakar, Nur Ain (2015)
The reformation of public sector roles under New Public Management (NPM) reform had encouraged public sector bodies to innovate and improve their organizational performance. Lean management practices are one of the quality innovation, which recently, have been gaining more attention from public sector bodies. Lean management practices comprise various tools and approach pertaining to quality improvement in the organisation. Thus, it is important to examine how lean management practices contribute to the organisational performance in the public sector. The purpose of this study is to examine the extent of lean management practices in local government in Malaysia, particularly city council effect on organisational performance in the area of organizational productivity and service delivery. In addition, this study will determine the effect of lean management practices on organisational performance in the area of organizational productivity and service delivery. This study is a quantitative study and it employs survey research as the method of research conducted. This study was conducted in city council located in Peninsular Malaysia as population. The data obtained from the questionnaire distributed to local government employee were analysed using Statistical Package for Social Science (SPSS) version 21.0. From descriptive analysis, it was found that 5-s is the approach that being practiced most in local government followed by value stream mapping and kaizen. Through simple regression analysis, it was found that, lean management practices in local government do affect organisational performance in term of organisational productivity and service delivery. This indicates that the quality improvement application in the public sector, such as lean management practices do affect to their organisational performance in organisational productivity and service delivery.